PENERAPAN TATA KELOLA KEUANGAN DI UNIVERSITAS ISLAM BATIK SURAKARTA UNTUK MEWUJUDKAN GOOD UNIVERSITY GOVERNANCE - harsono harsono (Jurnal Pendidikan Ilmu Sosial, 2016)
The research aims were: 1) to explore the financial system in Batik Islamic University (UNIBA) Surakarta. 2) To identify the financial managing technique that appropriate with the needs of UNIBA. This was the qualitative research. The data collection was conducted by interviewing several lecturers and staff of UNIBA and observation. The research found the financial managing technique in UNIBA was too simple. Therefore, UNIBA needed the new financial system to encourage the Good University Governance.Keywords: finance, university, good governance